Gel ink ball-point pen color follow-up sealant and preparation method thereof
By using ionized maleic anhydride grafted SEBS elastomer and modified nanoparticle dye in follower sealant, the problems of followerability, drop resistance and color stability are solved, and efficient and economical follow-up are achieved. Preparation of dynamic sealant to meet personalized needs.
Patent Information
- Application Number
- CN202411588110.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
When pursuing follower and drop resistance, existing follower sealants are difficult to take into account color stability and personalized needs, and there is a problem of incompatibility between thickeners and ink.
Ionized maleic anhydride grafted SEBS elastomer as thickening agent and provides color stability by modified nanoparticle dyes. The modified nanoparticle dyes are prepared by reverse phase microemulsion method and are coated with organic dye cores. Shell structure nanoparticles, modified with isobutyltriethoxysilane.
A neutral ink ballpoint pen color follower sealant with excellent follow-up and drop resistance is achieved. It has good color stability, can meet the personalized needs of consumers, and reduces the use of thickener and reduces costs.
Smart Images

Figure BDA0005124817380000111 
Figure BDA0005124817380000131
Abstract
Description
Technical Field
[0001] The invention relates to a neutral ink ballpoint pen colored follower sealant and a preparation method of the follower sealant. Background Art
[0002] Follow-up sealant (also called tail plug oil) is an indispensable material for the manufacture of neutral ink ballpoint pens. It is used to seal the ink at the tail of the pen tube to prevent the ink from flowing back or volatilizing, and to prevent the ink from overflowing when the pen core falls. The follow-up sealant is required to have good follow-up performance, that is, when writing, the follow-up sealant needs to follow in time when the ink interface in the oil tube of the pen core moves downward due to ink consumption, otherwise a fault will be formed and the ink will not be able to flow out continuously. At the same time, it is required that there is less residue on the inner wall of the oil tube to ensure that there is still enough follow-up sealant to protect the pen core until the ink is consumed. Generally speaking, follow-up sealants with lower viscosity have better follow-up performance, and follow-up sealants with higher viscosity have better drop resistance. There is a certain contradiction between the two. Most manufacturers' follow-up sealant products need to find a balance between the two.
[0003] In addition, most of the follow-up sealants on the market are colorless and transparent, and there are also two colors, yellow and orange. Other colors are relatively rare. This is because the colorant used in the follow-up sealant is an organic dye. As an organic dye in the follow-up sealant, it needs to match other components, and it must be able to withstand a certain temperature without fading, and have low affinity with the ink and cannot migrate into the ink. If the organic dye does not match the other components, it will appear that the dye is not suitable for the follow-up sealant system, which leads to the scarcity of follow-up sealant products of other colors, which cannot meet the personalized needs of consumers. Summary of the invention
[0004] The present invention aims to overcome the deficiencies of the prior art and provide a color follower sealant for a neutral ink ballpoint pen with excellent followability and drop resistance and stable color, and a preparation method thereof.
[0005] The object of the present invention is achieved through the following solutions:
[0006] A neutral ink ballpoint pen colored follower sealant, which comprises, by weight: 45.0 to 72.0 parts of base oil, 0.2 to 0.5 parts of antioxidant, 2.0 to 6.0 parts of modified nanoparticle dye and 25.0 to 50.0 parts of thickener;
[0007] The modified nanoparticle dye is prepared by modifying silicon dioxide-coated organic dye core-shell structure nanoparticles prepared by a reverse microemulsion method with isobutyltriethoxysilane.
[0008] The organic dye is a water-soluble organic dye, which may be one or a mixture of basic royal blue, basic scarlet G, basic royal green, rhodamine B, brilliant blue, lemon yellow, gentian violet, and sunset yellow.
[0009] The thickener is ionized maleic anhydride grafted SEBS elastomer (MA-g-SEBS).
[0010] The ionized maleic anhydride grafted SEBS elastomer is prepared by reacting a base oil dispersion of maleic anhydride grafted SEBS elastomer (MA-g-SEBS) with LiOH.
[0011] Since the terminal carboxyl groups of maleic anhydride grafted SEBS elastomer (MA-g-SEBS) are acidic, and most neutral inks are alkaline, maleic anhydride grafted SEBS elastomer (MA-g-SEBS) as a thickener of follow-up sealant will slowly react with neutral ink during long-term storage, showing ink crosstalk. Therefore, it is necessary to ionize it and generate carboxylate ions by reacting with lithium hydroxide.
[0012] The grafting rate of the maleic anhydride grafted SEBS elastomer (MA-g-SEBS) is 1.0-2.0%.
[0013] When the grafting rate is less than 1.0%, the affinity of the thickener to the inner wall of the pen core oil tube and the ink does not change significantly, and the follow-up sealant made with this thickener fails to achieve improved follow-up performance. When the grafting rate is greater than 2.0%, the hydrophilicity of the thickener is so significantly improved that the base oil is obviously precipitated after being added to the base oil and stored, which manifests as ink channeling.
[0014] The molecular weight of the maleic anhydride grafted SEBS elastomer is 30,000-50,000.
[0015] The base oil is one of mineral oil, dimethyl silicone oil and polyalphaolefin (PAO) oil.
[0016] The antioxidant is one of butylated hydroxybenzoic acid and tri-tert-butylated hydroxyanisole.
[0017] The viscosity of the follow-up sealant is 30000-50000 cp at a rotation speed of 6 rpm using a No. 4 rotor of a rotational viscometer.
[0018] The preparation method of the follower sealant of the present invention comprises the following steps:
[0019] (1) Preparation of modified nanoparticle dyes
[0020] Cyclohexane, n-hexanol and surfactant TritonX-100 are mixed uniformly in a certain proportion, and a proper amount of water is added as a dispersed phase. After stirring at room temperature for 15 to 25 minutes, a water-soluble organic dye is added as a core material, and then tetraethyl orthosilicate and ammonia water are added to the microemulsion system in a certain volume ratio. After continuous stirring and reaction for 24 hours, the particles are separated to obtain nanoparticle dyes;
[0021] The nanoparticle dye is added to anhydrous ethanol under stirring conditions, and after being evenly dispersed, the temperature is raised to 65-75° C., and 1.0-2.0% isobutyltriethoxysilane by weight of the nanoparticle dye is added under stirring conditions, and the mixture is reacted for 2-4 hours. After naturally cooling to room temperature, the solid substance is filtered out, and the solid substance is placed in an oven at 105-120° C. and dried for 10-12 hours to recover the modified nanoparticle dye;
[0022] Thickener preparation
[0023] The maleic anhydride grafted SEBS elastomer (MA-g-SEBS) particles are dispersed in a base oil at 85-95°C, a 20% LiOH aqueous solution is added, and the mixture is stirred at a constant temperature for 2-3 hours. After the reaction is completed, the mixture is dehydrated at 110-120°C and -0.07--0.09MPa for 40-60 minutes, activated carbon is added and stirred for 20-30 minutes to adsorb unreacted LiOH, and the activated carbon adsorbed with unreacted LiOH is removed by hot filtration, and the mixture is cooled to obtain a mixture of the base oil and the ionized maleic anhydride grafted SEBS elastomer dispersed in the base oil, which is a thickener;
[0024] (3) Preparation of follow-up sealant
[0025] Add the thickener to the base oil, raise the temperature to 130-170°C, and after the temperature reaches the target value, stir at a constant temperature for 30-90 minutes, then transfer to a high-speed disperser, disperse at a speed of 5000-8000 rpm for 30-60 minutes, add the modified nanoparticle dye, continue to disperse at high speed for 30-60 minutes, add the antioxidant, and then disperse at high speed for 20-40 minutes. After stopping the high-speed dispersion, cool to room temperature, and store in a vacuum drying oven for 40-48 hours to defoam, to obtain a follow-up sealant.
[0026] Compared with the prior art, the follower sealant of the present invention has the following advantages:
[0027] Ionized maleic anhydride grafted SEBS elastomer is used as the thickener of the follow-up sealant. The ionized maleic anhydride grafted SEBS elastomer is evenly distributed in the follow-up sealant. The polar groups of the end groups of the ionized maleic anhydride grafted SEBS elastomer are distributed in a dotted manner on the inner wall of the oil pipe, which does not damage the affinity between the follow-up sealant and the oil pipe as a whole, achieves good follow-up performance while ensuring anti-drop performance, and solves the contradiction between anti-drop performance and follow-up performance.
[0028] Modified nanoparticle dyes are used as colorants for follow-up sealants. The hydrophilic organic dyes are coated inside by the silica shell and further blocked by the non-polar base oil. They will not migrate into the ink. As the silica particles are dispersed throughout the follow-up sealant, they have excellent color stability. There is no need to conduct a lot of tests and spend time screening organic dyes that are compatible with the follow-up sealant system. Follow-up sealant products of various colors can be easily developed as needed to meet the personalized needs of consumers. In addition, the nano-silica shell of the modified nanoparticle dye also has a thickening effect, which can reduce the use of thickeners and thus reduce costs. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below according to specific embodiments. The protection scope of the present invention is not limited to the following embodiments, which are listed only for illustrative purposes and do not limit the present invention in any way.
[0030] Example 1
[0031] The preparation of the follow-up sealant in this embodiment includes the following steps:
[0032] (1) Preparation of modified nanoparticle dyes
[0033] 5 mL of surfactant Triton X-100 was dissolved in a mixture solution of 15 mL of cyclohexane and 5 mL of n-hexanol, 5 mL of alkaline royal blue aqueous solution with a mass concentration of 1% was added, and the mixture was stirred at room temperature for 20 min to obtain a reverse microemulsion, 0.3 mL of tetraethyl orthosilicate was added to the reverse microemulsion and stirred for 10 min, and then 0.3 mL of ammonia water was added, and the mixture was reacted at room temperature for 24 h under continuous stirring to obtain a reaction solution; the reaction solution was dripped dropwise into a round-bottom flask containing 25 mL of acetone, and then allowed to stand for 1 h, and the obtained mixture was placed in a centrifuge and centrifuged at 10000 rpm for 15 min, the supernatant was discarded, and the solid particles at the bottom were obtained, which were washed with deionized water for 3 times and dried in an oven at 80°C for 4 h to obtain a blue nanoparticle dye;
[0034] 30.0 g of the above blue nanoparticle dye was added to 70.0 g of anhydrous ethanol under stirring, and after being evenly dispersed, the temperature was raised to 65° C., and 0.3 g of isobutyltriethoxysilane was added under stirring, and the mixture was reacted for 2 h. After naturally cooling to room temperature, the solid substance was filtered out, and dried in an oven at 105° C. for 12 h, and the modified blue nanoparticle dye was recovered;
[0035] (2) Preparation of thickener
[0036] 4012g of mineral oil was added to a reactor, and the temperature was raised to 85°C. 1000g of maleic anhydride grafted SEBS elastomer (weight average molecular weight 30000, grafting rate 1.0%) was added under stirring to make it uniformly dispersed, 25.71g of 20% LiOH aqueous solution was added, and the mixture was stirred at a constant temperature for 3h. After the reaction was completed, the mixture was dehydrated at 110°C and -0.08MPa for 40min, 200g of activated carbon was added and stirred for 30min to adsorb unreacted LiOH, and the activated carbon adsorbed with unreacted LiOH was removed by hot filtration, and the temperature was lowered to obtain a mixture of base oil and ionized maleic anhydride grafted SEBS elastomer dispersed in the base oil, which was a thickener;
[0037] (3) Preparation of follow-up sealant
[0038] Add 25.0 g of the thickener prepared in step (2) to 70.8 g of mineral oil, heat to 130° C., stir at constant temperature for 90 min, transfer to a high-speed disperser, and disperse at high speed at 5000 rpm for 60 min. Add 4.0 g of the modified blue nanoparticle dye prepared in step (1), continue to disperse at high speed for 45 min, add 0.2 g of antioxidant butyl hydroxybenzoic acid, and disperse at high speed for another 40 min. Stop dispersing and cool to room temperature. Store in a vacuum drying oven for 48 h to defoam, and obtain a blue follow-up sealant.
[0039] Example 2
[0040] The preparation of the follow-up sealant in this embodiment includes the following steps:
[0041] (1) Preparation of modified nanoparticle dyes
[0042] Dissolve 5 mL of surfactant TritonX-100 in a mixture solution of 15 mL of cyclohexane and 5 mL of n-hexanol, add 5 mL of 1% alkaline red G aqueous solution, stir at room temperature for 15 min to obtain a reverse microemulsion, add 0.3 mL of ethyl orthosilicate to the reverse microemulsion and stir for 10 min, then add 0.3 mL of ammonia water, react at room temperature for 24 h under continuous stirring to obtain a reaction solution; drip the reaction solution drop by drop into a round-bottom flask containing 25 mL of acetone, let stand for 1 h, put the obtained mixture into a centrifuge and centrifuge at 10,000 rpm for 15 min, discard the supernatant, obtain the solid particles at the bottom, and wash with deionized water 3 times. Dry in an oven at 80°C for 2 h to obtain a red nanoparticle dye;
[0043] 30.0 g of the red nanoparticle dye was added to 70.0 g of anhydrous ethanol under stirring, and after being evenly dispersed, the temperature was raised to 75° C., and 0.5 g of isobutyltriethoxysilane was added under stirring, and the mixture was reacted for 2 h. After naturally cooling to room temperature, the solid was filtered to obtain a solid substance, which was placed in an oven at 120° C. and dried for 10 h to obtain a modified red nanoparticle dye;
[0044] (2) Preparation of thickener
[0045] 4018g of dimethyl silicone oil was added to a reactor, and the temperature was raised to 90°C. 1000g of maleic anhydride grafted SEBS elastomer (weight average molecular weight 40000, grafting rate 1.5%) was added under stirring to make it uniformly dispersed, 38.57g of 20% LiOH aqueous solution was added, and the mixture was stirred at a constant temperature for 3h. After the reaction was completed, the mixture was dehydrated at 110°C and -0.07MPa for 60min, 300g of activated carbon was added and stirred for 30min to adsorb unreacted LiOH, and the activated carbon adsorbed with unreacted LiOH was removed by hot filtration, and the temperature was lowered to obtain a mixture of base oil and ionized maleic anhydride grafted SEBS elastomer dispersed in the base oil, which was a thickener;
[0046] (3) Preparation of follow-up sealant
[0047] Add 37.5 g of the thickener prepared in step (2) to 60.2 g of dimethyl silicone oil, heat to 170° C., stir at constant temperature for 30 min, transfer to a high-speed disperser, and disperse at high speed for 45 min at 6500 rpm. Add 2.0 g of the modified red nanoparticle dye prepared in step (1), continue to disperse at high speed for 30 min, add 0.3 g of antioxidant butyl hydroxybenzoic acid, and disperse at high speed for another 20 min. Stop dispersing, cool to room temperature, and store in a vacuum drying oven for 48 h to defoam, to obtain a red follow-up sealant.
[0048] Example 3
[0049] The preparation of the follow-up sealant in this embodiment includes the following steps:
[0050] (1) Preparation of modified nanoparticle dyes
[0051] Dissolve 5 mL of surfactant TritonX-100 in a mixture of 15 mL of cyclohexane and 5 mL of n-hexanol, add 5 mL of 1% alkaline green aqueous solution, stir at room temperature for 25 min to obtain a reverse microemulsion, add 0.3 mL of tetraethyl orthosilicate to the reverse microemulsion and stir for 10 min, then add 0.3 mL of ammonia water, react at room temperature for 24 h under continuous stirring to obtain a reaction solution; drip the reaction solution dropwise into a round-bottom flask containing 25 mL of acetone, let stand for 1 h, put the obtained mixture into a centrifuge and centrifuge at 10,000 rpm for 15 min, discard the supernatant, obtain the solid particles at the bottom, and wash with deionized water 3 times. Dry in an oven at 80°C for 2 h to obtain a green nanoparticle dye;
[0052] 30.0 g of the green nanoparticle dye was added to 70.0 g of anhydrous ethanol under stirring, and after being evenly dispersed, the temperature was raised to 70° C., and 0.6 g of isobutyltriethoxysilane was added under stirring, and the mixture was reacted for 4 h. After naturally cooling to room temperature, the solid was filtered to obtain a solid substance, which was placed in an oven at 120° C. and dried for 10 h to obtain a modified green nanoparticle dye;
[0053] (4) Preparation of thickener
[0054] 4024g of dimerized alpha olefin (PAO 10) was added to a reactor, and the temperature was raised to 95°C. 1000g of maleic anhydride grafted SEBS elastomer (weight average molecular weight 50000, grafting rate 2.0%) was added under stirring to make it uniformly dispersed, 51.43g of 20% LiOH aqueous solution was added, and the mixture was stirred at constant temperature for 3h. After the reaction was completed, the mixture was dehydrated at 110°C and -0.09MPa for 40min, 200g of activated carbon was added and stirred for 30min to adsorb unreacted LiOH, and the activated carbon adsorbed with unreacted LiOH was removed by hot filtration, and the temperature was lowered to obtain a mixture of base oil and ionized maleic anhydride grafted SEBS elastomer dispersed in the base oil, which was a thickener;
[0055] (3) Preparation of follow-up sealant
[0056] Add 50.0 g of the thickener prepared in step (2) to 43.5 g of polyalphaolefin (PAO 10), heat to 150° C., stir at constant temperature for 60 min, transfer to a high-speed disperser, and disperse at high speed at 8000 rpm for 30 min. Add 6.0 g of the modified green nanoparticle dye prepared in step (1), continue to disperse at high speed for 60 min, add 0.5 g of antioxidant tri-tert-butylhydroxyanisole, and disperse at high speed for another 30 min. Stop dispersing, cool to room temperature, and store in a vacuum drying oven for 48 h to defoam, to obtain a green follow-up sealant.
[0057] Comparative Example 1
[0058] In this comparative example, the non-ionized maleic anhydride grafted SEBS elastomer (weight average molecular weight 30,000, grafting rate 1.0%) in Example (1 is used instead of the ionized maleic anhydride grafted SEBS elastomer prepared in Example (1) as a thickener, and the remaining additives and preparation process are the same as those in Example (1).
[0059] Comparative Example 2
[0060] This comparative example uses ungrafted SEBS elastomer particles as a thickener to prepare a follow-up sealant, comprising the following steps:
[0061] (1) Preparation of modified nanoparticle dyes
[0062] The preparation contents of the modified nanoparticle dye are the same as those in Example 1;
[0063] (2) Preparation of follow-up sealant
[0064] 25.0 g of ungrafted SEBS elastomer particles (weight average molecular weight 30,000) were added to 70.8 g of mineral oil, the temperature was raised to 130° C., and the mixture was stirred at a constant temperature for 90 min. The mixture was then transferred to a high-speed disperser and dispersed at a speed of 5,000 rpm for 60 min. 4.0 g of the blue modified nanoparticle dye prepared in step (1) was added and the high-speed dispersion was continued for 45 min. 0.2 g of antioxidant butyl hydroxybenzoic acid was added and the mixture was dispersed at a high speed for another 40 min. After the dispersion was stopped, the mixture was cooled to room temperature and stored in a vacuum drying oven for 48 h for defoaming to obtain a blue follow-up sealant.
[0065] Comparative Example 3
[0066] The preparation of the follow-up sealant of this comparative example comprises the following steps:
[0067] (1) Preparation of modified nanoparticle dyes
[0068] The preparation contents of the modified nanoparticle dye are the same as those in Example 1;
[0069] (2) Preparation of thickener
[0070] 4008g of mineral oil was added to a reactor, and the temperature was raised to 85°C. 1000g of maleic anhydride grafted SEBS elastomer (weight average molecular weight 30000, grafting rate 0.7%) was added under stirring to make it uniformly dispersed, 18.00g of 20% LiOH aqueous solution was added, and the mixture was stirred at a constant temperature for 3h. After the reaction was completed, the mixture was dehydrated at 110°C and -0.08MPa for 40min, 200g of activated carbon was added and stirred for 30min to adsorb unreacted LiOH, and the activated carbon adsorbed with unreacted LiOH was removed by hot filtration, and the temperature was lowered to obtain a mixture of base oil and ionized maleic anhydride grafted SEBS elastomer dispersed in the base oil, which was a thickener;
[0071] (3) Preparation of follow-up sealant
[0072] Add 25.0 g of the thickener prepared in step (2) to 70.8 g of mineral oil, heat to 130° C., stir at constant temperature for 90 min, transfer to a high-speed disperser, and disperse at high speed at 5000 rpm for 60 min. Add 4.0 g of the blue modified nanoparticle dye prepared in step (1), continue to disperse at high speed for 45 min, add 0.2 g of antioxidant butyl hydroxybenzoic acid, and disperse at high speed for another 40 min. Stop dispersing and cool to room temperature. Store in a vacuum drying oven for 48 h to defoam, and obtain a blue follow-up sealant.
[0073] Comparative Example 4
[0074] The preparation of the follow-up sealant of this comparative example comprises the following steps:
[0075] (1) Preparation of modified nanoparticle dyes
[0076] The preparation contents of the modified nanoparticle dye are the same as those in Example 1;
[0077] (2) Preparation of thickener
[0078] 4030g of mineral oil was added to a reactor, and the temperature was raised to 85°C. 1000g of maleic anhydride grafted SEBS elastomer (weight average molecular weight 30000, grafting rate 2.5%) was added under stirring to make it uniformly dispersed, 64.28g of 20% LiOH aqueous solution was added, and the mixture was stirred at a constant temperature for 3h. After the reaction was completed, the mixture was dehydrated at 110°C and -0.08MPa for 40min, 200g of activated carbon was added and stirred for 30min to adsorb unreacted LiOH, the activated carbon to remove unreacted LiOH was filtered while hot, and the temperature was lowered to obtain a mixture of base oil and ionized maleic anhydride grafted SEBS elastomer dispersed in the base oil, which was a thickener; the obtained ionized maleic anhydride grafted SEBS elastomer had a grafting rate of 2.5%.
[0079] (3) Preparation of follow-up sealant
[0080] Add 25.0 g of the thickener prepared in step (2) to 70.8 g of mineral oil, heat to 130° C., stir at constant temperature for 90 min, transfer to a high-speed disperser, and disperse at high speed at 5000 rpm for 60 min. Add 4.0 g of the blue modified nanoparticle dye prepared in step (1), continue to disperse at high speed for 45 min, add 0.2 g of antioxidant butyl hydroxybenzoic acid, and disperse at high speed for another 40 min. Stop dispersing and cool to room temperature. Store in a vacuum drying oven for 48 h to defoam, and obtain a blue follow-up sealant.
[0081] Comparative Example 5
[0082] The preparation of the follow-up sealant of this comparative example comprises the following steps:
[0083] (1) Preparation of modified nanoparticle dyes
[0084] The preparation contents of the modified nanoparticle dye are the same as those in Example 1;
[0085] (2) Preparation of thickener
[0086] The same preparation contents of the thickener as in Example 1;
[0087] (3) Preparation of follow-up sealant
[0088] Add 22.0 g of the thickener prepared in step (2) to 73.8 g of mineral oil, heat to 130° C., stir at constant temperature for 90 min, transfer to a high-speed disperser, and disperse at high speed at 5000 rpm for 60 min. Add 4.0 g of the modified nanoparticle dye prepared in step (1), continue to disperse at high speed for 45 min, add 0.2 g of antioxidant butyl hydroxybenzoic acid, and disperse at high speed for another 40 min. Stop dispersing and cool to room temperature. Store in a vacuum drying oven for 48 h to defoam, and obtain a blue follow-up sealant.
[0089] Comparative Example 6
[0090] The preparation of the follow-up sealant of this comparative example comprises the following steps:
[0091] (1) Preparation of modified nanoparticle dyes
[0092] The preparation contents of the modified nanoparticle dye are the same as those in Example 1;
[0093] (2) Preparation of thickener
[0094] The same preparation contents of the thickener as in Example 1;
[0095] (3) Preparation of follow-up sealant
[0096] Add 55.0 g of the thickener prepared in step (1) to 40.8 g of mineral oil, heat to 130° C., stir at constant temperature for 90 min, transfer to a high-speed disperser, and disperse at high speed at 5000 rpm for 60 min. Add 4.0 g of modified nanoparticle dye, continue to disperse at high speed for 45 min, add 0.2 g of antioxidant butyl hydroxybenzoic acid, and disperse at high speed for another 40 min. Stop high-speed dispersion and cool to room temperature. Store in a vacuum drying oven for 48 h to defoam, and obtain a blue follow-up sealant.
[0097] Comparative Example 7
[0098] This comparative example uses the same mass of modified silicon dioxide nanoparticles and oil-soluble blue dye to replace the modified nano-ionic dye for the preparation of the follow-up sealant, comprising the following steps:
[0099] (1) Preparation of modified silica nanoparticles
[0100] 5 mL of surfactant Triton X-100 was dissolved in a mixture solution of 15 mL of cyclohexane and 5 mL of n-hexanol, 5 mL of deionized water was added, and the mixture was stirred at room temperature for 20 min to obtain a reverse microemulsion, 0.3 mL of tetraethyl orthosilicate was added to the reverse microemulsion and stirred for 10 min, and then 0.3 mL of ammonia water was added, and the mixture was reacted at room temperature for 24 h under continuous stirring to obtain a reaction solution; the reaction solution was dripped dropwise into a round-bottom flask containing 25 mL of acetone, and then allowed to stand for 1 h, and the obtained mixture was placed in a centrifuge and centrifuged at 10,000 rpm for 15 min, the supernatant was discarded, and the solid particles at the bottom were obtained, which were washed with deionized water for 3 times and dried in an oven at 80°C for 4 h to obtain silica nanoparticles;
[0101] 30.0 g of the above silicon dioxide nanoparticles were added to 70.0 g of anhydrous ethanol under stirring conditions. After being evenly dispersed, the temperature was raised to 65° C., 0.3 g of isobutyltriethoxysilane was added under stirring conditions, and the mixture was reacted for 2 h. After naturally cooling to room temperature, the solid matter was filtered out, and dried in an oven at 105° C. for 12 h to recover the modified silicon dioxide nanoparticles.
[0102] (2) Preparation of thickener
[0103] The same preparation contents of the thickener as in Example 1;
[0104] (3) Preparation of follow-up sealant
[0105] 25.0g of the thickener prepared in step (2) was added to 70.8g of mineral oil, the temperature was raised to 130°C, the mixture was stirred at a constant temperature for 90min, and then transferred to a high-speed disperser for high-speed dispersion at 5000rpm for 60min. 3.96g of the modified silicon dioxide nanoparticles prepared in step (1) and 0.04g of the oil-soluble organic dye solvent blue 36 were added, and the high-speed dispersion was continued for 45min. 0.2g of antioxidant butyl hydroxybenzoic acid was added, and the mixture was dispersed at high speed for another 40min. After the high-speed dispersion was stopped, the mixture was cooled to room temperature and stored in a vacuum drying oven for 48h for defoaming to obtain a blue follow-up sealant.
[0106] Comparative Example 8
[0107] This comparative example adopts the thickener prepared in Example (1), replaces 4.0 g of the nanoparticle dye in Example (1) with 3.996 g of base oil and 0.004 g of oil-soluble blue dye, and prepares a follow-up sealant, comprising the following steps:
[0108] Add 25.0 g of the thickener prepared in step (2) to 74.76 g of mineral oil, heat to 130° C., stir at constant temperature for 90 min, transfer to a high-speed disperser, and disperse at high speed at 5000 rpm for 60 min. Add 0.04 g of oil-soluble organic dye Solvent Blue 36, continue to disperse at high speed for 45 min, add 0.2 g of antioxidant butyl hydroxybenzoic acid, and disperse at high speed for another 40 min. Stop high-speed dispersion, cool to room temperature, and store in a vacuum drying oven for 48 h to defoam, to obtain a blue follow-up sealant.
[0109] The weight of each additive added in the examples and comparative examples is shown in Table 1.
[0110] Table 1 Thickener grafting rate and quality of various additives of color follow-up sealant prepared in Example and Comparative Example
[0111]
[0112] *1: Comparative Example 7 uses 3.96g modified nano-silica + 0.04g oil-soluble blue dye instead of 4.0g nanoparticle dye
[0113] *2: Comparative Example 8 uses 3.96g base oil + 0.04g oil-soluble blue dye instead of 4.0g nanoparticle dye
[0114] The viscosities of the follow-up sealants prepared in the examples and comparative examples were tested at a rotation speed of 6 rpm using a No. 4 rotor of a rotational viscometer. The data are shown in Table 2.
[0115] Table 2 Viscosity data of color follow-up sealant 6rpm obtained in Examples and Comparative Examples
[0116] serial number Viscosity (6rpm, cp) Example 1 32640 Example 2 39650 Example 3 47820 Comparative Example 1 32940 Comparative Example 2 33260 Comparative Example 3 33130 Comparative Example 4 32150 Comparative Example 5 28370 Comparative Example 6 51320 Comparative Example 7 32470 Comparative Example 8 29720
[0117] The viscosity of the follow-up sealant of the embodiment at 6 rpm is in the range of 30000-50000 cp. The viscosity of the follow-up sealants of Comparative Examples 1, 2, 3 and 4 at 6 rpm is similar to that of Example 1. The thickening effects of the unionized maleic anhydride grafted SEBS elastomer of Comparative Example 1, the ungrafted SEBS elastomer of Comparative Example 2, and the ionized maleic anhydride grafted SEBS elastomers of Comparative Examples 3-4 with different grafting rates are basically similar. The maleic anhydride grafting reaction occurs at the end of the SEBS elastomer, which is only a small part relative to the ungrafted SEBS main chain and does not affect its thickening performance. Comparative Example 5 uses the same thickener as Example 1, but the added mass accounts for 22.0% of the whole, and the viscosity of the prepared follow-up sealant at 6 rpm is lower than 30000 cp. Comparative Example 6 uses the same thickener as Example 1, but the added mass accounts for 55.0% of the whole, and the viscosity of the prepared follow-up sealant at 6 rpm is higher than 50000 cp. Comparative Example 7 uses modified silica nanoparticles and oil-soluble dyes instead of modified nanoparticle dyes. The surfaces of modified silica nanoparticles and modified nanoparticle dyes are both modified silica, and have similar thickening properties. Comparative Example 8 uses base oil and oil-soluble dyes instead of modified nanoparticle dyes. The viscosity at 6 rpm is lower than that of Example 1, which shows that the modified nanoparticle dye has a thickening effect.
[0118] Commercially available neutral ink, pen tips, connections, oil pipes (inner diameter 2.75 mm), sheaths, and the follow-up sealants prepared in the embodiments and comparative examples were used to prepare the refills of neutral ink ballpoint pens (the follow-up sealant was poured into the tail end of the oil pipe). After centrifugation, the refills that opened normally were selected for the following application performance test and evaluated according to the standards. The evaluation results are shown in Table 3.
[0119] 1. Follow-up test
[0120] Take 5 refills and scribble on the scribing instrument at a scribing speed of 4.5m / min. After 400m scribing, measure the residual height of the follow-up sealant, and record the ratio of the residual height to the initial height as the residual rate. Take the average of the residual rates of the 5 refills. The higher the value, the better the follow-up performance.
[0121] When the ink consumption of the refill is the same, the smaller the inner diameter of the oil tube, the faster the ink will drop, and the higher the follow-up requirements of the follow-up sealant. The refill of the commercially available neutral ink ballpoint pen usually has a minimum inner diameter of 2.75mm, and the average residual rate is usually less than 50%.
[0122] 2. Drop resistance test
[0123] Drop the pen core from a height of 1m through a vertical pipe onto a 2cm thick fir board 10 times, observe the state of the follow-up sealant and evaluate it according to the following standards:
[0124] The follow-up sealant has no deformation: A;
[0125] The follow-up sealant is deformed and a small amount of ink penetrates into the sealant: B;
[0126] The follow-up sealant overflows from the pen core, and a large amount of ink seeps into the follow-up sealant: C.
[0127] 3. Ink leakage test when the pen core is placed upside down
[0128] In an environment of 50±1℃, keep the pen tip (with a sheath) upright for 30 days, and observe whether there is any phenomenon of the follower sealant leaking into the ink. The evaluation criteria are as follows:
[0129] No ink leakage: A;
[0130] Partial ink leakage: B;
[0131] Most ink spills: C.
[0132] 4. Drip performance test
[0133] In an environment of 50±1℃, keep the pen tip (with sheath) upright for 30 days, observe the degree of dripping of the follow-up sealant on the inner wall of the oil pipe and evaluate it according to the following standards:
[0134] No drip: A;
[0135] Some of the follow-up sealant drips to the tail of the oil pipe: B;
[0136] There is considerable dripping of the follower sealant and some of it flows out of the pen barrel: C.
[0137] 5. Color stability test
[0138] In an environment of 50±1℃, keep the pen tip (with sheath) square for 30 days, observe the color of the follow-up sealant and evaluate it according to the following standards:
[0139] No fading, no color stratification: A;
[0140] Slight fading or slight color delamination: B;
[0141] There is noticeable fading or obvious delamination: C.
[0142] Table 3 Application performance test results of neutral ink ballpoint pen refills made of follow-up sealants in embodiments and comparative examples
[0143]
[0144] The follow-up performance of the core of the neutral ink ballpoint pen made of the follow-up sealant in the embodiment is above 75%, that is, after the ink in the core is written, there is still enough follow-up sealant to ensure the anti-fall and anti-backflow of the core, and the other four tests are all A.
[0145] Comparative Example 1 uses un-ionized maleic anhydride grafted SEBS elastomer as a thickener to prepare a follow-up sealant, and the follow-up performance, anti-fall performance and dripping performance are all good, but the color stability is average, and the ink leakage performance of the pen core is poor. Comparative Example 2 uses un-grafted SEBS elastomer as a thickener to prepare a follow-up sealant, and the affinity with the inner wall of the pen core oil tube and the ink is poor, and the follow-up performance is the worst. The grafting rate of the ionized maleic anhydride grafted SEBS elastomer in the follow-up sealant of Comparative Example 3 is 0.7%, and the affinity of the thickener with the inner wall of the pen core oil tube and the ink does not change significantly. The follow-up sealant prepared using this thickener fails to achieve good follow-up performance. In the follow-up sealant of Comparative Example 4, the grafting rate of ionized maleic anhydride grafted SEBS elastomer is 2.5%, and the hydrophilicity of the thickener is significantly improved. The prepared follow-up sealant is applied to the refill of neutral ink ballpoint pen with good follow-up performance, but the anti-fall and dripping performance are general, and the refill has poor ink leakage performance. Comparative Example 5 adopts a low viscosity solution, and the follow-up performance is very good, but the anti-fall and dripping performance are very poor. Comparative Example 6 adopts a high viscosity solution, and the anti-fall performance is very good, but the follow-up performance is very poor. Comparative Example 7 uses modified silica nanoparticles and oil-soluble dyes instead of modified nanoparticle dyes. The follow-up performance, anti-fall performance, ink leakage and dripping performance of the refill are all good, but the color stability is poor. Comparative Example 8 uses base oil and oil-soluble dyes instead of modified nanoparticle dyes, and the follow-up performance and ink leakage performance of the refill are good, and the other items are poor. None of the comparative examples achieved good comprehensive performance.
[0146] Those skilled in the art should note that the embodiments described in the present invention are merely exemplary, and various other substitutions, changes and improvements may be made within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but only to the claims.
Claims
1. A neutral ink ballpoint pen color follower sealant, characterized in that: The color follower sealant comprises, by weight: 45.0 to 72.0 parts of base oil, 0.2 to 0.5 parts of antioxidant, 2.0 to 6.0 parts of modified nanoparticle dye and 25.0 to 50.0 parts of thickener; The modified nanoparticle dye is prepared by modifying the organic dye core-shell structure nanoparticles coated with silicon dioxide prepared by the reverse microemulsion method with isobutyltriethoxysilane.
2. The color follower sealant according to claim 1, characterized in that: The organic dye is a water-soluble organic dye, which may be one or a mixture of basic royal blue, basic scarlet G, basic royal green, rhodamine B, brilliant blue, lemon yellow, gentian violet, and sunset yellow.
3. The color follower sealant according to claim 1, characterized in that: The thickener is ionized maleic anhydride grafted SEBS elastomer (MA-g-SEBS).
4. The color follower sealant according to claim 3, characterized in that: The ionized maleic anhydride grafted SEBS elastomer is prepared by reacting a base oil dispersion of maleic anhydride grafted SEBS elastomer (MA-g-SEBS) with LiOH.
5. The color follower sealant according to any one of claims 3 to 4, characterized in that: The grafting rate of the maleic anhydride grafted SEBS elastomer (MA-g-SEBS) is 1.0-2.0%; the weight average molecular weight of the maleic anhydride grafted SEBS elastomer (MA-g-SEBS) is 30000-50000.
6. The color follower sealant according to claim 1, characterized in that: The base oil is one of mineral oil, dimethyl silicone oil and polyalphaolefin (PAO) oil.
7. The color follower sealant according to claim 1, characterized in that: The antioxidant is one of butylated hydroxybenzoic acid and tri-tert-butylated hydroxyanisole.
8. The color follower sealant according to claim 1, characterized in that: The viscosity of the color follow-up sealant is 30000-50000 cp at a rotation speed of 6 rpm using a No. 4 rotor of a rotational viscometer.
9. The method for preparing the color follow-up sealant according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Preparation of modified nanoparticle dyes Cyclohexane, n-hexanol and surfactant TritonX-100 are mixed uniformly in a certain proportion, and a proper amount of water is added as a dispersed phase. After stirring at room temperature for 15 to 25 minutes, a water-soluble organic dye is added as a core material, and then tetraethyl orthosilicate and ammonia water are added to the microemulsion system in a certain volume ratio. After continuous stirring and reaction for 24 hours, the particles are separated to obtain nanoparticle dyes; The nanoparticle dye is added to anhydrous ethanol under stirring conditions, and after being evenly dispersed, the temperature is raised to 65-75° C., and 1.0-2.0% isobutyltriethoxysilane by weight of the nanoparticle dye is added under stirring conditions, and the mixture is reacted for 2-4 hours. After naturally cooling to room temperature, the solid substance is filtered out, and the solid substance is placed in an oven at 105-120° C. and dried for 10-12 hours to recover the modified nanoparticle dye; Thickener preparation The maleic anhydride grafted SEBS elastomer (MA-g-SEBS) particles are dispersed in a base oil at 85-95°C, a 20% LiOH aqueous solution is added, and the mixture is stirred at a constant temperature for 2-3 hours. After the reaction is completed, the mixture is dehydrated at 110-120°C and -0.07--0.09MPa for 40-60 minutes, activated carbon is added and stirred for 20-30 minutes to adsorb unreacted LiOH, and the activated carbon adsorbed with unreacted LiOH is removed by hot filtration, and the mixture is cooled to obtain a base oil and an ionized maleic anhydride grafted SEBS elastomer dispersed in the base oil, which is a thickener; (3) Preparation of color follow-up sealant Add thickener to base oil, raise the temperature to 130-170°C, stir at constant temperature for 30-90 minutes after the temperature reaches the target value, transfer to high-speed disperser, disperse at 5000-8000rpm for 30-60 minutes, add modified nanoparticle dye, continue high-speed dispersion for 30-60 minutes, add antioxidant, and disperse at high speed for another 20-40 minutes. Stop high-speed dispersion and cool to room temperature, store in vacuum drying oven for 48 hours for defoaming, and obtain colored follow-up sealant.